2018
DOI: 10.1080/02699052.2018.1511067
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic impairment in chronic traumatic brain injury: examining the influence of cognitive load and injury severity

Abstract: This study provides additional support for the value of eye tracking for enhanced assessment of TBI. Additionally, findings suggest that TBI is associated with greatest susceptibility to oculomotor interference under high levels of cognitive load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…Importantly, the types of eye movements that are most strongly impacted by mTBI are those that most heavily rely upon effective cognitive processing, as opposed to measures of basic neuromotor function 14,18,27‐29 . In particular, previous research conducted by our group 14,15 and others 28‐30 has shown enhanced sensitivity of eye movements to effects of mTBI under conditions of increased cognitive load. Many oculomotor metrics are also less impacted by age, education, or intelligence, relative to conventional neuropsychological measures 20,31,32 …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Importantly, the types of eye movements that are most strongly impacted by mTBI are those that most heavily rely upon effective cognitive processing, as opposed to measures of basic neuromotor function 14,18,27‐29 . In particular, previous research conducted by our group 14,15 and others 28‐30 has shown enhanced sensitivity of eye movements to effects of mTBI under conditions of increased cognitive load. Many oculomotor metrics are also less impacted by age, education, or intelligence, relative to conventional neuropsychological measures 20,31,32 …”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive neuropsychological evaluation is a widely accepted approach for identification of functional neural impairment; 11 however, this approach generally returns “normal” results beyond 90 days postinjury 12‐15 . This raises questions about the value of neuropsychological assessment for the mTBI patient who seeks treatment after symptoms have become chronic.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations